Brand Experience on Brand Loyalty through Brand Satisfaction and Brand Trust: Study on Altex Cat Customers in East Java - Mustajab, Duta (Mahameru Publisher, 2023)
The paint industry in Indonesia is facing fierce competition from competitors and increasingly selective consumers. In this context, PT Atlantic Ocean Paint, a prominent company known for its product Altex, aims to understand customer needs and create positive brand experiences to foster brand loyalty and boost sales. This study, conducted in Papua Province, Indonesia, with 200 participants from various cities, explores how brand experience, brand satisfaction, and brand trust influence brand loyalty. Data was collected through a structured research instrument with validated scales for the mentioned variables. The findings indicate that brand experience directly affects brand satisfaction but not brand trust. Brand satisfaction, in turn, influences both brand trust and brand loyalty. However, brand experience does not have a direct impact on brand loyalty. Nevertheless, there is an indirect influence, as brand experience significantly affects brand loyalty through brand satisfaction and brand trust. By grasping these insights, PT Atlantic Ocean Paint can effectively enhance customer loyalty and improve its competitive edge in the challenging paint market in Indonesia.